(untitled) (Proceedings of the International Conference on Education, 2021)
International studies have reported that quality in patient care and safety, as well as the personal well-being of resident doctors, may suffer a detriment if a highly demanding or hostile clinical training environment is present. The objective of the Professionalism and Wellbeing Program for Medical Residents implemented by a university in northern Mexico is to integrate strategies for the development of wellbeing as a professional competence, and to contribute to strengthening clinical training environments, with the intention of improving personal selfcare, wellbeing, and patient care. The program was implemented with the 290 medical residents of the 17 specialty programs from March 2019 and, additionally, an hybrid model was implemented due to the COVID-19 pandemic from April 2020 to date. In February 2019 and 2020, medical residents participated in the induction sessions of the Professionalism and Wellbeing Program and at least in 3 sessions through the semester, in 2019 face-to-face and in 2020 virtually. The chiefs and co-chiefs of residents were trained in a Workshop so they could help other residents in adverse situations. Among the virtual strategies, we implemented an online website, an electronic form for residents´ wellbeing and mentoring follow-up, individual virtual counseling and Balint groups in Zoom. From April 2020 to February 2021, 220 residents registered online their wellbeing follow-up. The topics of greatest interest for discussion selected by the participants (n= 51) in the Balint group sessions were: emotional well-being in health professionals (94.1%) and burnout syndrome (94.1%). These initiatives aim to strengthen the training processes of education, professionalism, and humanism, with the residents as an expression of the social responsibility of the profession to contribute to selfcare, wellbeing, and patient’s care.